Design and fabrication of umbrella swing stand - Abdul Khaliq, Abdul Kadir (2010)
The device for removing water drops from an umbrella is constituted such that a number of water absorption members with elastic property are disposed at certain intervals radially in the inserting opening for an umbrella of the device body. The inserting space for the umbrella is in the central part of a number of absorption members, thereby a closed rainy umbrella is inserted into the inserting space. The umbrella cloth is inserted into clearance between the each adjacent water absorption member, and then water drops on the umbrella cloth can be absorbed and removed by sliding the inserted umbrella in the direction of insertion of the umbrella. The device does not need such energy as electric energy and water absorption is performed certainly and within only short time.